2009
DOI: 10.1001/jama.2009.853
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Factor V Leiden and Prothrombin G20210A in Adults With Venous Thromboembolism and in Family Members of Those With a Mutation

Abstract: LINICIANS TEST FOR PROTHROMbotic genetic mutations including factor V Leiden (FVL) (612309.001) and prothrombin G20210A (176930.0009) when treating patients who have had or are at risk of venous thromboembolism (VTE). Factor V Leiden refers to a single base change in the factor V gene (G1691A) that eliminates 1 of its 3 activated protein C cleavage sites. Consequently, factor V is inactivated at a lower rate, leading to more thrombin generation. 1 A single FVL allele is present in about 5%, 2.2%, and 1.2% of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
156
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(175 citation statements)
references
References 59 publications
9
156
0
10
Order By: Relevance
“…The mutant allele rs1799963*A was not detected in Afro-descendants individuals. These findings are in agreement with other reports showing that the prothrombin polymorphism varies among different ethnic groups, presenting a very low frequency in Afro-descendants (0.3%) 22 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The mutant allele rs1799963*A was not detected in Afro-descendants individuals. These findings are in agreement with other reports showing that the prothrombin polymorphism varies among different ethnic groups, presenting a very low frequency in Afro-descendants (0.3%) 22 .…”
Section: Discussionsupporting
confidence: 93%
“…The mutant allele rs1799963*A was not detected in Afro-descendants individuals. These findings are in agreement with other reports showing that the prothrombin polymorphism varies among different ethnic groups, presenting a very low frequency in Afro-descendants (0.3%) 22 .The frequencies of genotypes (98% for rs1799963*GG and 2% for rs1799963*GA) and alleles (99% for rs1799963*G and 1% for rs1799963*A) in northeastern Brazilian population (patients and control) observed in this study are consistent with results in other Brazilian subpopulations reported in previous studies. In fact, in general Brazilian population the mutant allele frequency ranged between 0.7%-3.6% (rs1799963*A) 23,24,25 .…”
supporting
confidence: 93%
“…Therefore, initial studies investigating CAT have focused on these “classical” targets. Factor V Leiden—a genetic variant that is resistant to inactivation by activated protein C—confers an increased risk of VTE with an odds ratio of 3.49 in the healthy population 31. While some studies suggest a two‐ to five‐fold increased risk of VTE in cancer patients with Factor V Leiden,32, 33, 34 other cohort studies were unable to confirm this association 35, 36, 37.…”
Section: Host‐specific Geneticsmentioning
confidence: 99%
“…A pooled analysis of the literature found the risk associated with factor V Leiden mutation to be significantly increased, but the magnitude was so modest that this by itself does not merit committing a patient to long-term anticoagulation (odds ratios of approximately 1.5 each for factor V Leiden and prothrombin G20210A). 15,16 Hereditary deficiencies of antithrombin, protein C, or protein S are much less frequently encountered in clinical practice, and one of these disorders will be identified in fewer than 5% of patients presenting with a first unprovoked episode of VTE; this is increased up to about 15% if the patient is under age 50 and has a positive family history. Patients with these less common thrombophilic defects may merit long-term anticoagulation, particularly if other first-degree family members have sustained VTE.…”
Section: Clinical Vignette: a 61-year-old Male In Excellent Health Sumentioning
confidence: 99%